Cheerleading and baton twirling. (New York Tempo Books/Grosset & Dunlap, 1979)
Contains illustrated instructions for basic cheerleading and baton twirling routines including yells, jumps, and twirls.
Keywords: Cheerleading -- Juvenile literature; Baton twirling -- Juvenile literature; Cheerleading; Baton twirling